Evaluation of Antigenic Comparisons Among BVDV Isolates as it Relates to Humoral and Cell Mediated Responses - Falkenberg, Shollie M.; Dassanayake, Rohana P.; Terhaar, Brett; Ridpath, Julia F.; Neill, John D.; Roth, James A. (Frontiers in Veterinary Science, 2021)
Antigenic differences between bovine viral diarrhea virus (BVDV) vaccine strains and field isolates can lead to reduced vaccine efficacy. Historically, antigenic differences among BVDV strains were evaluated using techniques based on polyclonal and monoclonal antibody activity. The most common method for antigenic comparison among BVDV isolates is determination of virus neutralization titer (VNT). BVDV antigenic comparisons using VNT only account for the humoral component of the adaptive immune response, and not cell mediated immunity (CMI) giving an incomplete picture of protective responses. Currently, little data is available regarding potential antigenic differences between BVDV vaccine strains and field isolates as measured by CMI responses. The goal of the current paper is to evaluate two groups of cattle that differed in the frequency they were vaccinated, to determine if similar trends in CMI responses exist within each respective group when stimulated with antigenically different BVDV strains. Data from the current study demonstrated variability in the CMI response is associated with the viral strain used for stimulation. Variability in IFN-γ mRNA expression was most pronounced in the CD4+ population, this was observed between the viruses within each respective BVDV subgenotype in the Group 1 calves. The increase in frequency of CD25+ cells and IFN-γ mRNA expression in the CD8+ and CD335+ populations were not as variable between BVDV strains used for stimulation in the Group 1 calves. Additionally, an inverse relationship between VNT and IFN-γ mRNA expression was observed, as the lowest VNT and highest IFN-γ mRNA expression was observed and vice versa, the highest VNT and lowest IFN-γ mRNA expression was observed. A similar trend regardless of vaccination status was observed between the two groups of calves, as the BVDV-1b strain had lower IFN-γ mRNA expression. Collectively, data from the current study and previous data support, protection against BVDV as a method for control of BVDV in cattle populations is still a complex issue and requires a multifactorial approach to understand factors associated with vaccine efficacy or vaccine failure. Although, there does appear to be an antigenic component associated with CMI responses as well as with humoral responses as determined by VNT.